Corporate carbon performance data: Quo vadis?. (24th April 2020) - Busch, Timo; Johnson, Matthew; Pioch, Thomas
Abstract: Corporate carbon performance (CCP) has become a central topic in political, financial, and academic domains. At the same time, several characteristics of CCP data, including comparability and consistency, remain unresolved. The literature has extensively covered issues regarding the comparability of CCP data from a firm‐internal perspective. However, it has not yet examined the consistency of CCP data between third‐party data providers. This article investigates the degree of CCP data consistency between third‐party providers according to three dimensions: scope (i.e., direct and indirect emissions), scheme (i.e., mandatory and voluntary reporting schemes), and source (i.e., data stemming from corporate reports and from third‐party estimation methods). The results reveal that data on direct emissions are more consistent than data on indirect emissions, and they are especially inconsistent for Scope 3. Second, mandatory and voluntary reporting schemes do not substantially improve the consistency of CCP data, which is surprising. Third, third‐party estimations are less consistent as compared to data stemming directly from corporate reports; however, the combination of Scopes 1 and 2 third‐party estimated data raises consistency levels. On the basis of these results, we conclude the following key implications: academic researchers must be mindful of the consistency of CCP data, because it can significantly affect empirical results, corporate management should avoid situations where different CCP data are communicated externally, investors should engage firms to follow a standardized approach, data providers should increase the transparency about their estimation methods, and policy makers need to be aware of the importance of a sound and standardized methodology to determine CCP.